A New Approach to the Problem of Business Cycles - Kalecki, M. (Review of Economic Studies, 1949)
Journal Article A New Approach to the Problem of Business Cycles Get access M. Kalecki M. Kalecki United Nations , Lake Success Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 16, Issue 2, 1949, Pages 57–64, https://doi.org/10.2307/2295715 Published: 01 January 1949